Access Control of EHR Records in a Heterogeneous Cloud Infrastructure - Szabó, Zoltán; Bilicki, Vilmos (Acta Cybernetica, 2021)
Since the advent of smartphones, IoT and cloud computing, we have seen an industry-wide requirement to integrate different healthcare applications with each other and with the cloud, connecting multiple institutions or even countries. But despite these trends, the domain of access control and security of sensitive healthcare data still raises a serious challenge for multiple developers and lacks the necessary definitions to create a general security framework addressing these issues. Taking into account newer, more special cases, such as the popular heterogeneous infrastructures with a combination of public and private clouds, fog computing, Internet of Things, the area becomes more and more complicated. In this paper we will introduce a categorization of these required policies, describe an infrastructure as a possible solution to these security challenges, and finally evaluate it with a set of policies based on real-world requirements.